Estate Planning and the Reality of Perpetuities Problems Today: Reliance upon Statutory Reform and Saving Clauses is Not Enough - David M. Becker (Washington University Law Quarterly, 1986)
The purpose of this Article is to demonstrate the current relevance of the common-law rule against perpetuities; first, by illustrating the prominence of perpetuities problems, and second, by considering various planning solutions to these problems. It concentrates on these problems in relation to the lawyer's role as a planner. This creative function is the most important one in the estate transfer process because it sets the framework by which dispositive goals are to be achieved, assets are to be conserved, and disputes are to be avoided. Consequently, it is here that lawyers first and most frequently encounter perpetuities problems and the common-law rule. It is within this context that lawyers often disregard it; nevertheless, it is precisely here the lawyers must not shrink from addressing it.
Keywords: Estate planning; Perpetuities